Clinically-assisted hydration in patients in the last days of life (?CHELSEA II? trial): a cluster randomised trial - Davies, Andrew (My University, 2022)
Introduction Provision of clinically assisted hydration (CAH) at the end of life is one of the most contentious issues in medicine. The aim of the ‘CHELsea II’ trial is to evaluate CAH in patients in the last days of life. The objectives are to assess the effect of CAH on delirium, audible upper airway secretions, pain and other symptoms, and overall survival, as well as the tolerability of CAH, and the health economic impact. Methods and analysis The study is a cluster randomised trial, involving 80 sites/clusters (mainly hospices) and 1600 patients. Sites will be randomised to an intervention, and this will become the standard of care during the trial. Intervention ‘A’ involves continuance of drinking (if appropriate), mouth care and usual end-of-life care. Intervention ‘B’ involves continuance of drinking, mouth care, usual end-of-life care and CAH, that is, parenteral fluids. The fluid may be given intravenously or subcutaneously, the type will be dextrose saline (4% dextrose, 0.18% sodium chloride) and the volume will be dependent on weight. Participants will be assessed every 4 hours by the clinical team. The primary endpoint is the proportion of participants who develop delirium determined using the Nursing Delirium Screening Scale (using a cut-off score of ≥2). A mixed-effects logistic regression will be used to assess the difference in the odds of developing delirium between the interventions. Ethics and dissemination Ethical committee approval has been granted by the Brighton and Sussex Research Ethics Committee (REC) (main REC for the UK: reference—IRAS 313640), and by the Scotland A REC (REC for adults with incapacity in Scotland: reference—22/SS/0053-IRAS-317637). The consent process follows the Mental Capacity Act: if the patient has capacity, then consent will be sought in the normal way; if the patient does not have capacity, then a personal/nominated consultee will be approached for advice about the patient entering the study. The consent process is slightly different in Scotland. The results of the trial will be published in general medical/palliative care journals, and presented at general medical/palliative care conferences.
PUBLISHED
Keywords: clinically assisted hydration; End of life care; palliative care